Nanodiamonds/poly(vinylidene fluoride) composites for tissue engineering applications - Pereira, Eduardo Jorge Nunes (2017)
Poly (vinylidene fluoride) (PVDF) composites with different types of nanodiamond (ND) particles were produced by solvent casting. The variations of the morphological, structural, optical, thermal and electrical properties of the composites were studied as a function of nanofiller type (without and with air oxidation treatment) and concentration (in the range 0.11 wt%). No noticeable differences were found in the polymer crystallization process, the processing conditions and the filler determining the morphology and structure of the polymer. Nevertheless, ND nanofillers were useful for the tailoring of the optical properties, and also slightly contributed to the thermodynamic stability of the samples. An increase in the dielectric constant (2) of the ND composites, while maintaining constant the dielectric losses, was observed, independently of the filler concentration. On the other hand, solvent casted porous composites crystallize mainly in the electroactive -phase of PVDF. Those composite membranes were evaluated with pre-osteoblast culture tests and these revealed that the inclusion of ND nanoparticles does not induce cytotoxicity on the samples. Taking advantage of the properties of the polymer for cell culture and with the potential of the ND filler for protein functionalization and drug delivery, it is concluded that NDs/PVDF composites are a suitable platform for biomedical applications.